Losartan-associated toothache in a patient with diabetes and hypertension: a hypothesis-generating case report - Yuan, Li; Tang, Mingxue; Liao, Shuaiju; Xiang, Dan; Liu, Tao; Wang, Yangtian (Frontiers in Pharmacology, 2025)
BackgroundAngiotensin II receptor blockers (ARBs) are standard of care for hypertensive patients, particularly those with type 2 diabetes mellitus (T2D). Although generally well tolerated, rare adverse drug reactions can be overlooked. To our knowledge, no prior case report up to 2025 has described isolated toothache attributable to losartan.Case PresentationA 45-year-old man with T2D and essential hypertension developed a reproducible, diffuse maxillary toothache ≈30 min after each 50 mg dose of losartan potassium. Oral examination and panoramic radiography found no odontogenic pathology; routine laboratory tests were unremarkable. Symptoms resolved upon drug withdrawal and reappeared with supervised re-challenge; no recurrence occurred after substitution with candesartan. The Naranjo algorithm yielded a score of 7, supportive of a drug-related event, though causality cannot be proven in a single case.ConclusionThis observation is hypothesis-generating and suggests that losartan may rarely be associated with toothache. Recognizing this possibility may prevent unnecessary dental procedures and guide ARB substitution when appropriate. Systematic pharmacovigilance and mechanistic research are warranted.